2018
DOI: 10.1186/s12885-018-4207-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between time elapsed since completion of radiotherapy and quality of life of patients with breast cancer

Abstract: BackgroundTo investigate the relationship between time elapsed since completion of radiotherapy (RT) and quality of life (QOL) of patients with breast cancer.MethodsA total of 300 patients with breast cancer were treated at the First Affiliated Hospital of Anhui Medical University between January 2013 and April 2016. Of these, 212 patients were included in the study. Patients were divided into 4 groups based on the time elapsed since completion of RT. The generic cancer questionnaire, EORTC QLQ-30, and the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
6
5
0
Order By: Relevance
“…However, there were some patient related factors like body mass index and breast size, that influenced the occurrence of moist desquamation as well [28]. For arm symptoms after radiotherapy in breast cancer patients, no significant changes over time were reported by others [25,26,29]. This is in line with the present study, demonstrating differences for arm symptoms between the two study arms, but no significant changes over time.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, there were some patient related factors like body mass index and breast size, that influenced the occurrence of moist desquamation as well [28]. For arm symptoms after radiotherapy in breast cancer patients, no significant changes over time were reported by others [25,26,29]. This is in line with the present study, demonstrating differences for arm symptoms between the two study arms, but no significant changes over time.…”
Section: Discussionsupporting
confidence: 88%
“…In breast cancer survivors, it is well documented that radiotherapy may increase pain symptoms and that pain symptoms are significantly associated with poorer QoL [24]. Patient-reported pain after radiotherapy and the recovery of pain scores over time during follow-up, as seen in the 3-D-CRT-seqB group, was also confirmed by others [25][26][27]. Moist desquamation may be one reason for pain after radiotherapy of the breast, and seems to appear more often and to last longer in patients treated with standard radiotherapy compared to IMRT: In a multicenter, randomized clinical trial of Pignol et al testing the potential impact of IMRT on reducing acute skin reaction in comparison to standard wedge radiotherapy, the use of IMRT resulted in a significantly decreased risk of moist desquamation, which was associated with less pain.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Only four, of the 35, studies assessed the time elapsed between diagnosis and first/baseline testing and controlled for it in their analyses (28, 29, 33, 47). Future studies should consider controlling for this important factor in their analyses as this information has considerable relevance for quality of life outcomes due to expected consequences of specific treatments and for efforts to identify the expected rehabilitative needs of cancer survivors (50).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the relationship between social support and QoL is well-established (5154), where social support is associated with improved QoL and is shown to influence the patients' level of perceived distress related to their cancer diagnosis, which in turn may alter their evaluation of their outcomes, future studies should consider controlling for its contribution to the presence or absence of response shift in patient reported outcomes (12, 5154). Other important factors such as cancer type (found to be a statistically significant contributor in one of the three studies that reported it) and stage (a significant contributor in one of the five studies who examined it), the presence of comorbidities (found significant in two of the three studies who assessed it), occupation (evaluated in two studies), and marital status (found to be statistically significant in two of three studies who evaluated it) which have been documented to be associated with QoL outcomes among various cancer types, should be considered as possible confounds and included in future studies evaluating response shift given their considerable relevance to QoL outcomes among cancer patients due to efforts to identify modifiable and non-modifiable life factors in better survivorship (50). Lastly, we note the lack of standardization in the measurement and reporting of response shift in the studies reviewed here.…”
Section: Discussionmentioning
confidence: 99%